Arso Jovanović – an erased biography - Vukelić, Vlatka; Šumanović, Vladimir (Balcanica Posnaniensia. Acta et studia, 2019)
The article presents a basic overview of the war record of the chief of the Supreme Staff of the Partisan army Arso Jovanović. Jovanović's war biography is described in relation to three social groups in which he had operated. The first social group was the Piper clan, or the local Montenegrin context in which he was born and grew up. The other social group was the leadership of the Communist Party of Yugoslavia (KPJ) with which he cooperated during the war. The third social group was the circle of Montenegrin generals of the Yugoslav army (JA) which Jovanović belonged o until his unexplained death in the summer of 1948. This paper describes how all these groups were interlinked through Jovanović, how they affected each other creating the preconditions for the events of World War II and the post-war period in Yugoslavia.